Identi-city: A place for the spirits. - Dire, Boitumelo (My University, 2013)
In Africa and the diaspora, the legacy of European cultural imperialism and decades of colonial rule, have given rise to various anti-colonial discourses on identity, which not only seek to liberate Africans from the tyranny of western abstract universalism but also to reassert the legitimacy of all and every sphere of African thought and life, or what Okwui Enwezor refers to as a “liberated African modernity” (Enwezor, 2001,13-14) It is for this very reason and more that this thesis focuses on Indigenous African healing Practices in the city. As a young black African modern woman, I am conflicted by the ever changing world in relation to my culture, tradition and identity. It is this very complexity that the thesis aims to explore. The question came to me, two years ago, what than is this Liberated African modernity? As I walk through Faraday the feeling is not a pleasant one, but rather one that excludes me and my unidentified self. The journey to a space of this calibre is one that is to (from expectation) diminish the stereotypes that have circulated traditional healing, but instead it heightens the uncertainty and uneasiness of me being part of this old age ritual. It is addressing the complexity of this unidentified cultural epidemic that the thesis aims to ask the question what is liberated African modernity and its idenitity? Hence the field of architecture and planning considering apartheid spatial planning, creation of Bantustans that sought to “preserve” an “authentic African, tribal identity”, it seems to be the appropriate evidence to explore and engage with the question. Consequently, very little has been written in architectural discourses about the ways in which modern Africans negotiate their identities within the contemporary city. The thesis will be taking this phenomenon and negotiating through the discourses by proposing an Identi-City: Mixed used Spiritual Healing Hub, where various modern retail activities and traditional medical activities can occur, within the context of contemporary Johannesburg. The project is about African identies and the complexities that exist in relation to modernity and tradition. How these are conceptualized into the physical environment of the contemporary city, such as Johannesburg. Furthermore it is to look into the residues of the Apartheid system and the way black African Sangomas have spacalized themselves in the contemporary city. On the other hand there needs to start a new spacial language, in the way African modern identity is represented, through diverse celebratory spaces and Identi-City is about experiencing and identifying with these modern African spaces.